2018
DOI: 10.1002/jaba.508
|View full text |Cite
|
Sign up to set email alerts
|

A review of environmental enrichment as treatment for problem behavior maintained by automatic reinforcement

Abstract: We reviewed studies that used environmental enrichment as treatment for problem behavior maintained by automatic reinforcement. A search of behavior analytic journals produced 71 publications with a total of 265 applications of environmental enrichment used alone or in conjunction with alternative behavior manipulations (e.g., prompting, reinforcement) and problem behavior manipulations (e.g., blocking, restraint). Environmental enrichment, as a sole intervention, was efficacious in 41% of the sample. Alternat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(18 citation statements)
references
References 46 publications
0
18
0
Order By: Relevance
“…It was also compared across stimuli the authors characterized as “matched/unmatched,” stimulus type (food vs. nonfood), and functional classes of PB. For each CSA application, we also identified the percentage of stimuli assessed that produced a greater than 80% reduction in PB, which is a commonly used criterion of treatment efficacy in reviews of behavioral research (e.g., Gover et al, 2019; Kahng et al, 2002; Kurtz et al, 2003; Rooker et al, 2013). Both percentages were compared to the variables reported in Tables 1 and 2 (i.e., participant characteristics and CSA method, respectively).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…It was also compared across stimuli the authors characterized as “matched/unmatched,” stimulus type (food vs. nonfood), and functional classes of PB. For each CSA application, we also identified the percentage of stimuli assessed that produced a greater than 80% reduction in PB, which is a commonly used criterion of treatment efficacy in reviews of behavioral research (e.g., Gover et al, 2019; Kahng et al, 2002; Kurtz et al, 2003; Rooker et al, 2013). Both percentages were compared to the variables reported in Tables 1 and 2 (i.e., participant characteristics and CSA method, respectively).…”
Section: Methodsmentioning
confidence: 99%
“…Over the last two decades, CSAs have become a frequently used pretreatment assessment for a variety of topographies of automatically maintained PB (Gover et al, 2019; Rooker et al, 2018), and their use has been extended to the treatment of socially maintained PB. These CSAs are similar to those of automatically maintained PB, except social reinforcers are provided contingent on PB during all test and control trials.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…While interventions using noncontingent access to items are often successful alone, for some subjects, it is necessary to combine noncontingent access to items with a procedure designed to implement sensory extinction, such as blocking, protective equipment, or redirection (Gover, Fahmie, & McKeown, 2019; Rooker, Bonner, Dillon, & Zarcone, 2018). For example, Roscoe et al found substantial decreases in problem behavior maintained by automatic reinforcement when they presented subjects with noncontingent access to leisure items as a sole treatment component for only 7 of 14 subjects.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, it is sometimes not possible to place the behavior on extinction or readily prescribe a function‐based treatment. Instead, interventions such as environmental enrichment (i.e., noncontingent access to preferred items), response blocking, or response interruption and redirection are commonly used to reduce the occurrence of automatically reinforced behavior (Gover, Fahmie, & McKeown, ; Martinez & Betz, ; Saini et al, ).…”
mentioning
confidence: 99%